The influence of socioeconomic deprivation on outcomes in pancreas transplantation. (13th March 2015) - Khalid, Usman; Laftsidis, Prodromos; Chapman, Dawn; Stephens, Michael R.; Asderakis, Argiris
Abstract Socioeconomic deprivation is an important factor in determining poor health and is associated with a higher prevalence of many chronic diseases including diabetes and renal failure, with poorer outcomes of their treatments. The influence of deprivation on outcomes following pancreas transplantation has not previously been reported. The Welsh Index of Multiple Deprivation was used to assess the influence of socioeconomic deprivation on outcomes for 119 consecutive pancreas transplant recipients from a single center in the United Kingdom, transplanted between 2004 and 2013. Outcomes measured were rate of acute rejection and graft survival. Thirty‐five (29.4%) patients experienced at least one episode of acute rejection following their transplant. Rejection rates in least deprived were 37% and most deprived 24% (p = 0.29). Within the individual domains, rejection rate was higher for the "physical environment" domain (least deprived 40% vs. most deprived 17% (p = 0.053). Five‐year graft survival for least and most deprived groups was 75% and 88%, respectively (log‐rank test p‐value 0.24). This study has not demonstrated any significant differences in outcomes following pancreas transplantation in Wales in relation to socioeconomic deprivation with the exception possibly of the "physical environment" domain. Further studies with larger patient population or concentrating on physical environment deprivation would be of interest.